2019
DOI: 10.1177/0886260519851222
|View full text |Cite
|
Sign up to set email alerts
|

Male Role Norms, Heavy Drinking, and Bystander Behavior for Sexual Aggression

Abstract: Bystander training programs have proliferated on college campuses to prevent alcohol and non–alcohol-related sexual aggression. However, many programs fail to address the effects of a bystander’s alcohol use on intervention. This is not surprising due to the limited research examining this association. To this end, the present study examined how heavy drinking and a known correlate of intervention, men’s adherence to traditional masculinity, are jointly and independently associated with bystander behavior in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…This reflects benevolent sexist attitudes towards women in adherence to traditional gender norms (see Glick & Fiske, 1996). This finding exposes a hidden dilemma with bystander programs that encourage men to intervene because it is possible that they could reinforce stereotypical gender beliefs if men assist women because they see themselves as protectors of women (see Leone & Parrott, 2021).…”
Section: Stage 3 -Take Responsibilitymentioning
confidence: 99%
“…This reflects benevolent sexist attitudes towards women in adherence to traditional gender norms (see Glick & Fiske, 1996). This finding exposes a hidden dilemma with bystander programs that encourage men to intervene because it is possible that they could reinforce stereotypical gender beliefs if men assist women because they see themselves as protectors of women (see Leone & Parrott, 2021).…”
Section: Stage 3 -Take Responsibilitymentioning
confidence: 99%
“…In this regard, Leone and Parrot (36) assert that men may feel pressured to adhere to manly norms they proscribe, and alcohol intoxication probably facilitates their attention to these signals, which strengthens this association. An example of this is the study by Dumbili et al (37), in which men agreed that drinking is for social reasons, and for other reasons such as engaging in sexual negotiations, displaying masculinity, and obtaining social attention.…”
Section: Affirming Masculinity With Alcohol Consumptionmentioning
confidence: 99%
“…This stereotype has been reinforced by traditional views, where drinking is associated with masculinity and abstention with femininity (40). This association has also led to a significant interaction between antifemininity and excessive alcohol consumption (36). In some cases, male identity is constructed through the role of protector of women, which involves a discussion of physical strength (41).…”
Section: Affirming Masculinity With Alcohol Consumptionmentioning
confidence: 99%
“…Additionally, research has found that alcohol use is associated with lower rates of prosocial bystander attitudes (Orchowski et al, 2016), while increasing an intoxicated person’s self-efficacy to intervene (Leone et al, 2022). However, it does appear that people who are intoxicated or are frequent heavy drinkers intervene less frequently (Fleming et al, 2015; Leone et al, 2019; Orchoswki et al, 2018). Overall, it appears that alcohol use is an important element to consider in understanding bystander opportunities and actions.…”
Section: Factors That Might Influence the Use Of Bystander Behaviorsmentioning
confidence: 99%